Goodenough-Harris Drawing a Man Test (GHDAMT) as a Substitute of Ages - Baraheni, Nasrin; Heidarabadi, Seifollah; Nemati, Shahrooz; Ghojazadeh, Morteza (Iranian Journal of Child Neurology, 2018)
Abstract Objective: Evaluation of concurrent validity of GHDAMT with the problem solving subscale of ASQ2 among 5 years old children was the objective of present research. Materials &Methods: In a cross sectional study 136 boy and 105 girl were selected randomly from childcares and tested with GHDAMT and ASQ2 to compare the concurrent validity of these tests in evaluation of cognition. Data was analyzed using SPSS.16/win. Results: The IQ mean difference in girls was 128±18.18 and in boys 118±18.50, which was statistically significant. There was no statistical significant correlation between GHDAMT and ASQ2. It was significant between IQ and mental age among children who had -2SD score in problem solving subscale, but there was no correlation between children who had -1SD score. These findings revealed that the GHDAMT does not have acceptable validity and concurrent validity of the test was less than 0.3. Conclusions: In the current research, there is no statistical significant correlation between problem solving subscale of ASQ2 and mental age and IQ. So GHDAMT can̕ t be used as a substitute of ASQ questionnaire; however, correlation of two tests in children with intellectual disability was meaningful. After further studies, it is possible to use GHDAMT as a proper tool for cognition evaluation of these children. Keywords: concurrent validity, The Goodenough-Harris drawing a man test, ASQ2